Time-resolved role of P2X4 and P2X7 during CD8+ T cell activation - Brock, Valerie J.; Lory, Niels Christian; Möckl, Franziska; Birus, Melina; Stähler, Tobias; Woelk, Lena-Marie; Jaeckstein, Michelle; Heeren, Joerg; Koch-Nolte, Friedrich; Rissiek, Björn; Mittrücker, Hans-Willi; Guse, Andreas H.; et al. (Frontiers in Immunology, 2024)
CD8+ T cells are a crucial part of the adaptive immune system, responsible for combating intracellular pathogens and tumor cells. The initial activation of T cells involves the formation of highly dynamic Ca2+ microdomains. Recently, purinergic signaling was shown to be involved in the formation of the initial Ca2+ microdomains in CD4+ T cells. In this study, the role of purinergic cation channels, particularly P2X4 and P2X7, in CD8+ T cell signaling from initial events to downstream responses was investigated, focusing on various aspects of T cell activation, including Ca2+ microdomains, global Ca2+ responses, NFAT-1 translocation, cytokine expression, and proliferation. While Ca2+ microdomain formation was significantly reduced in the first milliseconds to seconds in CD8+ T cells lacking P2X4 and P2X7 channels, global Ca2+ responses over minutes were comparable between wild-type (WT) and knockout cells. However, the onset velocity was reduced in P2X4-deficient cells, and P2X4, as well as P2X7-deficient cells, exhibited a delayed response to reach a certain level of free cytosolic Ca2+ concentration ([Ca2+]i). NFAT-1 translocation, a crucial transcription factor in T cell activation, was also impaired in CD8+ T cells lacking P2X4 and P2X7. In addition, the expression of IFN-γ, a major pro-inflammatory cytokine produced by activated CD8+ T cells, and Nur77, a negative regulator of T cell activation, were significantly reduced 18h post-stimulation in the knockout cells. In line, proliferation of T cells after 3 days was also impaired in the absence of P2X4 and P2X7 channels. In summary, the study demonstrates that purinergic signaling through P2X4 and P2X7 enhances initial Ca2+ events during CD8+ T cell activation and plays a crucial role in regulating downstream responses, including NFAT-1 translocation, cytokine expression, and proliferation on multiple timescales. These findings suggest that targeting purinergic signaling pathways may offer potential therapeutic interventions.